Bamboo, Rattan and Sustainable Development - International Bamboo and Rattan Organisation (2020)
The first issue of Bamboo and Rattan Update looks at bamboo and rattan for sustainable development. The issue features articles from a number of key experts in the field of bamboo’s research and use, from the 1950s onwards, including: